1992
DOI: 10.1111/j.1476-5381.1992.tb13409.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of cyclic GMP in non‐adrenergic, non‐cholinergic inhibitory neurotransmission in dog proximal colon

Abstract: 1 Nitric oxide (NO) may serve as a non-adrenergic, non-cholinergic (NANC) neurotransmitter released from enteric inhibitory nerves in the gastrointestinal tract. We tested whether guanosine 3':5'-cyclic monophosphate (cyclic GMP) may serve as a second messenger in transducing the NO signal into inhibitory junction potentials (ij.ps) and relaxation in the canine proximal colon. 2 The membrane permeable analogue of cyclic GMP, 8-bromo cyclic GMP mimicked the effects of NO by hyperpolarizing cells near the myent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 38 publications
6
66
0
1
Order By: Relevance
“…The resulting solution was neutralized and kept on ice in an airtight container for the remainder of the day; solutions were prepared daily. Control experiments employing addition of vehicle or direct addition of NO (by addition of NO saturated water; see Ward et al, 1992) verified that the effect of CysNO was due to the delivery of NO.…”
Section: Preparation Of the Nitric Oxide Donor Cysnomentioning
confidence: 88%
See 1 more Smart Citation
“…The resulting solution was neutralized and kept on ice in an airtight container for the remainder of the day; solutions were prepared daily. Control experiments employing addition of vehicle or direct addition of NO (by addition of NO saturated water; see Ward et al, 1992) verified that the effect of CysNO was due to the delivery of NO.…”
Section: Preparation Of the Nitric Oxide Donor Cysnomentioning
confidence: 88%
“…Although nitric oxide (NO) has been found to play a role in the regulation of vascular (Furchgott & Zawadzki, 1980;Palmer et al, 1987) and nonvascular (Ward et al, 1992;Kannan & Johnson, 1992;Thornbury et al, 1992) smooth muscle tone, inhibition of platelet aggregation (Azuma et al, 1986), and the mediation of some immunological responses (Moncada et al, 1991), its role in the control of uterine smooth muscle contractility has yet to be fully characterized. Studies have been performed in the rat (Papka & McNeill, 1992;Shew et al, 1993;Natuzzi et al, 1993;Izumi et al, 1993;Conrad et al, 1993;Yallampalli et al, 1993;Franchi et al, 1994), guinea-pig (Weiner et al, 1994), human subjects (Izumi et al, 1993;Telfer et al, 1995;Buhimschi et al, 1995) and rabbit (Sladek et al, 1993) which suggest that the uterus is an NOproducing organ.…”
Section: Introductionmentioning
confidence: 99%
“…These observations indicate that the rapid relaxation in response to vagal stimulation was mediated by the release of NO. Methylene Blue has been reported to be a selective inhibitor of soluble guanylate cyclase, the proposed site of action of NO (Ward et al 1992;Chakder & Rattan, 1993). Baccari et al (1992) demonstrated that in the atropine-and guanethidinetreated animals, vagally mediated rebound contraction was depressed by prostaglandin synthesis inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…62,127,[191][192][193][194][195][196][197] Numerous studies have shown responses to NO in the GI tract depend upon the production of cyclic GMP (cGMP) by soluble guanylate cyclase. [198][199][200] Guanylate cyclase is a heterodimer comprised of 2 subunits, α and β. Using immunohistochemistry Iino et al 182,201 showed that both subunits are strongly expressed in ICC but not resolved in smooth muscle.…”
Section: Functional Evidence Demonstrating the Importance Of Interstimentioning
confidence: 99%